Enantioselective Total Synthesis of Dysidavarone A, a Novel Sesquiterpenoid Quinone from the Marine Sponge Dysidea avara. Issue 9 (30th January 2014) - Fukui, Yurie; Narita, Koichi; Katoh, Tadashi
Abstract Dysidavarone A, a structurally unprecedented sesquiterpenoid quinone, was synthesized in 30 % overall yield in a longest liner sequence of 13 steps from commercially available o‐vanillin. A highly strained and bridged eight‐membered carbocyclic core was established by the C7C21 carbon bond formation through a copper enolate mediated Michael addition to the internal quinone ring.